EXPERIENCES OF FINAL-YEAR NURSING STUDENTS AT A PUBLIC INSTITUTION IN THE EASTERN CAPE PROVINCE REGARDING THEIR PREPAREDNESS TO BECOME PROFESSIONAL NURSES - Seekoe, E (South African Journal of Higher Education, 2016)
The purpose of this article is to describe experiences of final-year students at a public college of nursing regarding their preparedness to become registered nurses and to recommend actions to enhance the preparation of nursing students for transition. A qualitative, exploratory and descriptive research design was utilised to reach the objectives of the study of 27 purposively selected final-year nursing students. The results indicated that most of final-year nursing students experienced lack of preparedness to assume the professional nurse’s role with regard to certain factors, including: curriculum-related aspects; and equipment and library resources during nursing students’ training. Some experienced adequate preparedness in relation to role competency such as patient care. Nursing students lacked confidence and expressed apprehension about meeting the performance expectations of the workplace. The researcher recommends the identification of learning needs, their consideration, and contribution to the periodical review of the curriculum; reinstatement of clinical preceptors; standardisation of procedures; formulation of procedure manuals and delegation of finalists for managerial duties.